الممارسات المقيدة للمنافسة وآلية الرقابة عليها في ظل قانون المنافسة الجزائري - خضير, عبد الكريم (جامعة الوادي -University eloued, 2017)
حظر المشرع الجزائري الممارسات المقيدة للمنافسة بموجب المواد من 6الى 12 من الامر03-03 المتعلق بالمنافسة المعدل والمتمم، والتي تتمثل في الاتفاقات المقيدة للمنافسة و الممارسات التعسفية (التعسف في وضعية الهيمنة الاقتصادية والتعسف في وضعية التبعية الاقتصادية والتعسف في ممارسة أسعار بيع مخفضة تعسفيا). وأنشأ بمقتضى هذا القانون سلطة ضبط ورقابة لمتابعة هذه الممارسات وتوقيع العقوبات المقررة. ومن هنا لا يتسنى لهذا الجهاز العمل بكفاءة للوقاية من هذه الممارسات والضبط الفعال للسوق إلا من خلال مده بجميع الوسائل اللازمة المادية والمعنوية والاستفادة من تجارب الدول السباقة في هذا المجال وكذا التعاون الدولي في مجال المنافسة. The Algerian legislator is prohibited the restrictive practices of competition from 6 to 12 articles of Ordinance 03-03 modified and supplemented with respect to the competition which are the restrictive agreements of the competition and the practices of the abuses (the abuse of a dominant position Economic abuse, abuse of economic dependency and the practice of low pricing of selling). The implementation Under This Law, the regulatory authority and Control follows this practices and takes the penalties provided for. It is impossible for this authority to work effectively and to prevent these practices and effective market control only by a period with all the necessary equipment and moral means and to benefit from the experience of the pioneer countries in this field as well as the International cooperation in the field of compétition
ماستر اعمال
Keywords: الممارسات المقيدة للمنافسة –الاتفاقات المقيدة للمنافية -التعسف في وضعية الهيمنة الاقتصادية -التعسف في وضعية التبعية الاقتصادية-التعسف في ممارسة أسعار بيع مخفضة تعسفيا-سلطة; Restrictive practices of competition - agreements restricting competition - abuse of economic dominance - abuse of state of economic dependence - abuse